INTEGRATION OF HALAL TOURISM AND GREEN ECONOMY: SYSTEMATIC LITERATURE REVIEW FOR SYNERGY TRENDS IN SUSTAINABILITY PRACTICES - Muhammad Akbar; Rita Yunus; Nurfadilah Sindika Sari; Muhammad Ichsan (JURNAL PROFIT, 2025)
This research aims to explore the relationship between halal tourism and the green economy and its contribution to sustainable development and the local economy. The main purpose of this study is to analyze research trends, the relationship between these two sectors, research gaps related to the integration of halal tourism with the green economy, as well as patterns and thematic relationships between the main keywords in the existing literature. The Systematic Literature Review (SLR) approach and bibliometric analysis using the VOSviewer tool were applied to assess research trends, citation patterns, and the linkages between key concepts in the literature from 2016 to February 2025. The results of the analysis show that halal tourism that integrates green economic principles can reduce negative impacts on the environment, increase the use of local products, and support sustainable economic growth. The close relationship between halal tourism and the green economy is found in the VOSviewer analysis, with key clusters and keywords covering concepts such as sustainable development, sustainability, sustainable tourism and environmental. However, the research gap is seen in the lack of explicit integration between halal tourism and the green economy. Thematic patterns show a link between halal tourism, green economy, and sustainability, although research linking the three is still limited. This research contributes to understanding how halal tourism can serve as a sustainable tourism model that not only meets the needs of Muslim tourists, but also supports social, economic, and environmental sustainability. These findings lead to the need for the development of policies that better support the integration of these two sectors in industrial practice.